Manual not included - Baldwin, Hilaria (Gallery Books, 2025)
"There's no set of instructions when it comes to navigating the challenges life throws at us. However, by sharing our narratives and finding our commonality, we can better deal with what comes our way.In Manual Not Included, Hilaria writes about the relatable, hard-earned insights she's gained from her experiences as an individual, a partner, and a parent--from feeling empowered, to having a fulfilling relationship, to being as good a mother as possible, all while still being a work in progress. Within chapters about love, motherhood,and friendship, Hilaria offers up her candid stories around common themes facing women--from feeling like you're too much and also not enough, to grappling with the expectation to be a "good girl," and to striving for unattainable perfection. While there is no one right way to live, by sharing what we've learned along the way, with compassion and without judgment, we can each create our own perfectly imperfect manual."--